Orthogonally functionalizable maleimide based styrenic polymers - Yılmaz, İdil İpek. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Polymers containing maleimide groups on their side chains have been synthesized by utilization of a novel styrenic monomer containing a masked maleimide unit. Diels-Alder reaction between furan and maleimide was adapted for the protection of the reactive maleimide double bond in the monomer prior to polymerization. AIBN initiated free radical polymerization was utilized for synthesis of copolymers containing masked maleimide groups. No unmasking of the maleimide group was evidenced under the polymerization conditions. The maleimide groups in the side chain of the polymers were unmasked into their reactive form by utilization of retro Diels-Alder reaction. This cycloreversion was monitored by thermo gravimetric analysis (TGA), 1H and 13C NMR spectroscopy. Orthogonally multifunctional styrene based copolymers were obtained by copolymerization of the maleimide based monomer both with N-hydroxysuccinimide containing styrene monomer and alkene containing styrene monomer. Further functionalization studies were performed with two different thiols by using both Michael addition and thiol-ene click chemistry. Crosslinking studies for maleimide based styrenic copolymers were also performed as an extension of the project. Furfuryl amine was introduced to the polymer and the solution was spin coated on to the silicon surfaces. By heating the surface under vacuum, first Diels-Alder reaction between maleimide and furfuryl amine occured, then, due to the Michael addition of amines to free maleimides, crosslinked network was obtained. Remaining unreacted maleimides were functionalized both with bodipy bromide as a control and bodipy thiol. Fluorescence microscopy was used to investigate the degree of immobilization.
Keywords: Polystyrene.; Diels-Alder reaction.